Range Findings of Lethal Concentration of Zinc Sulfate Heptahydrate (ZnSO4.7H2O) to Juvenile Red Tilapia (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
An acute toxicity study was conducted to determine the range of lethal concentration of zinc sulfate heptahydrate (ZnSO4.7H2O) to juvenile red tilapia (Oreochromis sp.). The mortality of the fish was recorded at 24, 48, 72, and 96 hours of study. The lethal concentration of ZnSO4.7H2O that caused 50% mortality (LC50) was 48.7, 40.0, 34.6, and 33.1 mg/L for 24, 48, 72, and 96 hours, respectively. Meanwhile, the lethal concentration that caused 99% mortality (LC99) was 116.7, 108.7, 76.2, and 69.9 mg/L for 24, 48, 72, and 96 hours, respectively. The Probit analysis with a 95% confidence interval is used to determine the range of lethal concentration of ZnSO4.7H2O for 24, 48, 72, and 96 hours of toxicity study. The result shows that the lethal concentration of ZnSO4.7H2O decreased over time indicating that the low concentration could become lethal to juvenile red tilapia when exposed for longer periods and act as a preliminary study for further study.
Keywords: Juvenile Red Tilapia; Oreochromis sp; Zinc Sulfate; Lethal concentration; Toxicity